Use of computer facilities to develop students' English in Petaling and Hulu Langat secondary schools - Drabble, Gwynneth (1988)
Malaysian schools are encouraged to acquire computers, and use then to teach English. However, most teachers have not been trained to do this, so computer-assisted instruction may not be taking place. The interview and questionnaire techniques were used to survey the computer hardware and software available in computer clubs in government secondary school sin the Petaling and Hulu Langat districts of Selangor Daru Ehsan, and investigate how these facilities were used to develop students' English. Frequency counts were made, and the median was used to measure central tendency. Ninety percent of the target schools had computer clubs, with a median of 9.5 computers per club. Most computers were Apple or IBM compatible. Few schools used software specifically written to teach English. However,several programs with language-teaching potential, such as content-free packages,and packages using English on the screen, were used.